Cone Beam CT Assessment of Bone Width of Upper and Lower Jaws for Dental Implant Placement: An Iraqi Study. (13th April 2023) - Khazaal Al-Jaboori, Aseel S.; Hassan, Nuhad A.
Abstract : Background . Implantology focuses on the measurement of bone thickness in both the lower and upper jaws. This study aimed to measure and compare alveolar bone thickness of the upper and lower jaws at single edentate sites and cortical bone thickness of their mesial and distal dentate sites. Methods . Thickness of alveolar bone thickness was measured in 80 upper and 80 lower implant edentate sites and that of buccal and lingual cortical plates of their mesial and distal dentate sites using Cone beam CT. The bone thickness of the edentulous sites was recorded at 3 points (crestal bone, five mm from the crest, and ten mm from the crest), while the bone thickness of the dentate sites was determined at four points (crestal bone, midroot bone, mid of the alveolar bone housing, and apical portion). Results . An increased amount of bone was measured from the crest to the apical portion of the dentate sites on the buccal and lingual sides of both jaws with a highly significant difference detected among all the tested points (P < 0.0001 ). No statistical difference was detected between the means of buccal bone width at the first 3 points, except at point 4 (the apical portion), where the mean of the lower jaw (3.35 ± 0.54) was significantly larger than that of the upper jaw (3.17 ± 0.55) (P = 0.04 ). Bone width measured in the edentulous sites showed a gradual increase from the crest to the apical portions in both jaws. Conclusion . Bone thickness at the coronal levels is low and susceptible to resorption compared to the apical portions regardless of the dentate state.